The Strategy of Phytoplankton on Critical Conditions in Coastal Waters - Rahmadi Tambaru; Muh. Farid Samawi; Khairul Amri (International Journal of Agriculture System, 2020)
The productivity of phytoplankton found best in coastal waters is on a critical aquatic environmental condition for the life of phytoplankton (incubation time : 10.00-14.00). At that incubation time, the sun reached the apex of illumination (12.00). Theoretically, the best productivity is unlikely to happen because the activity of phytoplankton is not perfect. To answer that doubt, the research deals with the strategy of life phytoplankton on critical conditions in coastal waters. To achieve the desired results, multivariate analysis is used Correspondent analysis (CA) and Principal Components Analysis (PCA). The results showed that based on the analysis of Factorial Koresponde (CA), there were two grouping of phytoplankton  abundance. Group I showed that the grouping of phytoplankton  abundance of occurred at A depth of 10 m at the sampling  time A (10.00 : normal conditions). Group II occurs at a depth of 5 and 15 m at sampling time B (14.00: critical condition). Furthermore, the shift in grouping phytoplankton occurs at the sampling  time A at a depth of 10 m into the sampling time B in 5 m depth, not at at a depth of 0 m. This is due to the very strong sunlight intensity that can lead to death in the genera of phytoplankton that exist. It turns out that the strategy and the dynamics of phytoplankton abundance at critical time is not doing the grouping at the surface depth (0 m), but at a deeper depth (5 m) in order to keep the activity well done.